1997
DOI: 10.1016/s0735-1097(96)00501-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Activity at Onset of Symptoms and Outcome of Acute Myocardial Infarction

Abstract: There is an association between activity at onset and outcome of acute myocardial infarction. Differences in pathophysiology or in the population at risk could explain this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…20 In patients with preinfarction Braunwald class IIIB unstable angina, perhaps even a mild extrinsic stimulus can trigger the onset of AMI, suggesting that such patients have a lower threshold for abrupt coronary occlusion owing to the presence of vulnerable plaques. Physical activity at the onset of AMI has been associated with the severity of vascular disease, 19 and in the present study, patients with preinfarction stable angina had a slightly, but not significantly, higher incidence of multivessel disease.…”
Section: Physical Activity At the Onset Of Amisupporting
confidence: 51%
See 1 more Smart Citation
“…20 In patients with preinfarction Braunwald class IIIB unstable angina, perhaps even a mild extrinsic stimulus can trigger the onset of AMI, suggesting that such patients have a lower threshold for abrupt coronary occlusion owing to the presence of vulnerable plaques. Physical activity at the onset of AMI has been associated with the severity of vascular disease, 19 and in the present study, patients with preinfarction stable angina had a slightly, but not significantly, higher incidence of multivessel disease.…”
Section: Physical Activity At the Onset Of Amisupporting
confidence: 51%
“…Previous studies have shown that patients with preinfarction angina less frequently have symptom onset during exercise than those without prior angina at the onset of AMI. 18,19 These observations might simply reflect reduced daily physical activity in patients with preinfarction angina, especially those with rest angina, but Muller et al have suggested that hemodynamic or vasoconstrictive forces generated by physical or psychologic stress might disrupt vulnerable plaques. 20 In patients with preinfarction Braunwald class IIIB unstable angina, perhaps even a mild extrinsic stimulus can trigger the onset of AMI, suggesting that such patients have a lower threshold for abrupt coronary occlusion owing to the presence of vulnerable plaques.…”
Section: Physical Activity At the Onset Of Amimentioning
confidence: 99%
“…Information on the presence of triggers was obtained from interviews conducted by trained research personnel [17,22 -24,27,29,30], nurses and interns [19,21,28,31], medical staff [26,32], the attending cardiologist [25], the author herself [18] or undefined [16,20]. Some authors [21,22,28,29] precisely quantified the degree of physical activity on a scale from 1 to 8 metabolic equivalents (MET).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, physical activity was categorized as mild-to-moderate (3 to 5 MET), heavy ( z 6 MET) or any (either mild-to-moderate or heavy; z 3 MET). Some authors [26,31] did not distinguish between types of physical activity, reporting on both activity types as one category. The triggering events defined as meal [16], overeating [17,28,31] or eating and drinking [25] in the meta-analysis were included within the ''eating'' category.…”
Section: Methodsmentioning
confidence: 99%
“…INTERHEART includes large numbers of individuals from all regions of the world and multiple ethnicities, making the results broadly applicable, unlike previous studies of potential triggers that were performed primarily in 1 country or region. 9,16,[18][19][20][21]39,[43][44][45][46][47] IN-TERHEART also includes only participants with first AMI, thereby reducing the possibility that altered lifestyles or risk factors resulting from previous AMI would affect our estimates. In addition, sensitivity analyses including the controls from INTERHEART using multivariable-adjusted conditional logistic regression yielded similar associations.…”
mentioning
confidence: 99%